The learning field concept -- focus on problems and chances. - Muster-Wäbs H; Schneider K (PR-Internet fur die Pflege, 2005)
The learning field concept is influenced by two trends, i.e. from the dynamics in the working sphere and from realizations of the theories about learning. Therefore the question arises about the emergence of the learning field concept, which is understood by learning field concepts, which requirements and problems result in the case of the conversion and which role the teacher personality plays.